The analysis of pre-service physics teachers on basic teaching competencies through Peer Assessment - Muhammad Minan Chusni; Suyatman Suyatman (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2023)
The study was intended to analyze the profile of the skills of first-year students, students, and physics teacher candidates in the physics of building RPGS. The method used in this study is descriptive research. With research samples of class c microteaching students semester completed in 2022. In this study, data is generated from the performance of a mutual friend (mance) in cycle 1 and cycle 2. Data collection techniques with observations are used using peer assessments. The assessment of the student's basic skills score for asked-teacher physics in drafting RPP and teaching on cycle 1 has an average score of 89.5. Then after a friendly assessment is made on cycle two, the average score is 22.6. Based on the analysis, it was learned that a peer assessment could improve a student science candidate's skills in coming up with a plan of learning and skills in teaching. It was concluded that student physics teachers already had good skills in coming up with the learning plan and implementing it by teaching